Material characteristics and bending performance of glued laminated timber made of local lumbers - Zuo, Yuening (2019)
Glued-laminated timber, or glulam in short, is a structural timber component used widely nowadays as a popular construction material. With the laminating and gluing process, glulam specimen owns more favorable features including better controlled defects, variable scales and spans, as well as relatively higher strength, as compared to conventional solid timber materials. This report shows the investigations on strength and stiffness properties of glulam beams made of local species, as according to Eurocode 5 and corresponding BS codes. Five species were selected and three batches of three-point bending experiments were conducted, including two batches of prism beam tests, and one batch of the double-tapered beam test. Strength results and failure modes were compared with previous estimations, and improvements were made after first batch of prism beam testing in order to achieve a better result. The first batch of prism beams showed a complete failure by debonding of glue, and later improvements on glue applied as well as preparation of specimens on the second batch, were proved to be useful. Modulus of elasticity and bending strength were both approaching the expected results according to British Standards. The estimation using Eurocode 5 for the double tapered beam tests was also proved to be generally accurate.